Hubungan Kadar Hemoglobin (Hb) Dengan Derajat Diabetic Foot Ulcers (DFU) Di Kabupaten Bone - Alfian Mas'ud; Najman Najman (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: Vascular assessment, including the assessment of hemoglobin (Hb) levels or anemia, is a very important part of the treatment of Diabetic Foot Ulcers (DFU). However, several studies have shown different results regarding the relationship of Hemoglobin as a DFU wound healing factor.This study was to determine the relationship between hemoglobin levels and the degree of Diabetic Foot Ulcers (DFU).Methods: The design of this study was an analytic observational study in which the research subjects were Diabetic Foot Ulcers (DFU) patients undergoing treatment at a nurse's independent practice clinic in Bone Regency). The independent variable is hemoglobin level while the dependent variable is the degree of injury according to Meggitt Wagner's classification. The sampling technique used was the total sampling method.Results: This study was conducted in the independent practice of nurses in Bone Regency and involved 30 samples that met the inclusion and exclusion criteria. Data on hemoglobin levels and severity of Diabetic Foot Ulcers (DFU) were obtained from direct observation. Furthermore, the data were analyzed descriptively and tested with Spearman correlation. Spearman correlation test results obtained p = 0.083 (p> 0.05) and r = -0.322.Conclusion: there is a negative but not significant relationship between hemoglobin levels and the severity of diabetic ulcers with a weak correlation strength level. The lower the hemoglobin level, the more severe the severity of the ulcer.